Association of depression with sleep quality might be greater than that of pain intensity among outpatients with chronic low back pain - Wang H; Fu T; Hsu S; Hung C (Neuropsychiatric Disease and Treatment, 2016)
Hsin-Yu Wang,1,2,* Tsai-Sheng Fu,2,3,* Shih-Chieh Hsu,1,2 Ching-I Hung1,2 1Department of Psychiatry, Chang Gung Memorial Hospital at Linkou, Taoyuan, 2Chang Gung University College of Medicine, Taoyuan, 3Department of Orthopedics, Chang Gung Memorial Hospital at Keelung, Taiwan, Republic of China *These authors contributed equally to this work Purpose: No study to date has compared the associations of pain intensity, depression, and anxiety with insomnia among outpatients with chronic low back pain (CLBP). This study aimed to investigate this issue.Patients and methods: A total of 225 outpatients with CLBP were enrolled from a general orthopedics clinic. The Insomnia Severity Index was used to evaluate sleep quality. Major depressive disorder (MDD) and anxiety disorders were diagnosed using the Structured Clinical Interview for Diagnostic and Statistical Manual of Mental Disorders, fourth edition, text revision, Axis I Disorders. Two psychometric scales were used to evaluate depression and anxiety. The Visual Analog Scale was employed to assess pain intensity. Multiple linear regressions were performed to determine the association of insomnia with pain intensity, depression, and anxiety.Results: Among the 225 subjects, 58 (25.8%) had clinical insomnia; 83 (36.9%) had severe low back pain; 49 (21.8%) had MDD, including 21 (9.3%) with a current major depressive episode (MDE); and 52 (23.1%) had anxiety disorders. More than half (56.9%) of the subjects with CLBP and clinical insomnia had MDD and/or anxiety disorders. Subjects with a current MDE or anxiety disorders had greater severities of pain and insomnia as compared with subjects without these conditions. After controlling for demographic variables, MDE was more strongly associated with insomnia than severe low back pain; moreover, the severity of depression had a greater association with insomnia than pain intensity.Conclusion: The association of depression with insomnia was not inferior to that of pain intensity with insomnia. Among patients with CLBP and insomnia, integration of depression and anxiety treatment into treatment of pain might help to improve sleep quality. Keywords: depressive disorder, anxiety, sleep quality, backache, insomnia